Обстановка на Ближнем Востоке, или начало третьей мировой войны - Бермухамедов, А.У. (My University, 2013)
This article describes the situation in the Middle East as it is the epicenter of fight of some states for receiving control over Middle Eastern oil. Syria in the center fight of region, and this fight has to conduct to a new alignment of forces in two interames ted pats of world. All these events can lead us to the Third world war.